Fiscal Vulnerability and Financial Crises in Emerging Market Economies - Hemming, Richard (Occasional Papers; Occasional Paper ;, 2003)
Fiscal problems have long been considered a central feature of financial--that is, currency, debt, and banking--crises. This paper addresses four questions: What are the fiscal causes of crises? Which fiscal vulnerability indicators help to predict crises? Can fiscal variables explain the severity of crises? And what are the fiscal consequences of crises? Its findings are based on statistical analysis of a large data set of fiscal variables for 29 emerging market economies over 1970-2000 and detailed case studies of 11 emerging market crises during the 1990s that focus on structural and institutional dimensions of fiscal vulnerability.